Pengaturan Hukum Pidana di Indonesia Terhadap Penyalahgunaan Teknologi Artificial Intelligence Deepfake Dalam Melakukan Tindak Pidana Cybercrime - Patricia Morisa Banfatin; Karolus Kopong Medan; Debi F.Ng. Fallo (Pemuliaan Keadilan, 2025)
The development of artificial intelligence deepfake technology has opened up new opportunities in various fields to help speed up human work. However, on the other hand, this technology can also be misused to commit crimes. This research is a Normative Juridical research with a statutory approach and a conceptual approach, and examines the sources of legal materials according to the main problem, and uses prescriptive analysis techniques.The results of the study show: (1) The activity of using artificial intelligence deepfake technology that can cause cybercrime occurs due to attacks on the system, namely AI botnet attacks that have been infected by malicious software and Generative Adversarial Network attacks that have artificial neural networks that can produce data that is similar to the original data so that it is used as a means of committing crimes, and (2) Criminal law regulations in Indonesia regarding the misuse of artificial intelligence deepfake technology in committing cybercrime have not been regulated comprehensively, so that currently it is necessary to establish clear legal regulations in order to provide legal protection for every community.